2017
DOI: 10.4038/sljer.v5i1.58
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the role of agricultural extension services in improving technical efficiency in the paddy farming sector in Sri Lanka

Abstract: The overall aim of this study is to identify the role of agricultural extension services in improving technical efficiency in the rice farming sector in Sri Lanka. Accordingly, the study attempts to investigate how the agricultural extension service received by the farmers can improve technical efficiency (TE), using 200 farm-level data points in Ampara district in Sri Lanka. The Stochastic Production Frontier approach is used to estimate technical efficiency. Results show that the mean TE of rice farming in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Their studies showed that household education considerably reduced production inefficiencies. Services for agricultural extension can raise productivity among participants and level of living by educating farmers on how to use resources (such as inputs and technology) effectively, as shown by the positive correlation between their impact and technical efficiency (Athukorala, 2017). A similar relationship exists between agricultural productivity in emerging countries and the impact of agricultural extension services (Haq, 2013).…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Their studies showed that household education considerably reduced production inefficiencies. Services for agricultural extension can raise productivity among participants and level of living by educating farmers on how to use resources (such as inputs and technology) effectively, as shown by the positive correlation between their impact and technical efficiency (Athukorala, 2017). A similar relationship exists between agricultural productivity in emerging countries and the impact of agricultural extension services (Haq, 2013).…”
Section: Literature Reviewmentioning
confidence: 97%
“…However, the nation still lacks sustainable agricultural growth, and the farmers had low human capital (Adem & Gebregziabher, 2014). Consequently, agricultural extensions are necessary to promote faster output and rural revenue by quickening the spread of new technology (Athukorala, 2017). According to Haq (2013), who described the nation's current agricultural scenario, farmers now employ more irrigation and chemical fertilizers than they did in the past.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings show that output can be boosted by 21.5 percent without increasing input, and that access to high-quality extension services has the greatest influence on tea production's technical efficiency. Wasantha Athukorala(2017) studied the role of agricultural extension services in improving technical efficiency in the paddy farming sector in Sri Lanka and discovered that the mean technical efficiency of rice farming in the study area is 0.61, indicating that there is room to increase output by 39% without increasing input. Muditha Karunarathna (2014) looked at commercial vegetable producers who only grow a few distinct types of vegetables on their farms.…”
Section: Efficiency Studies Based On the Parametric Analysismentioning
confidence: 99%
“…21 . The effect of agricultural extension is positively associated with technical efficiency, and it is shown that the agricultural extension service can enhance farmers’ productivity and livelihood by educating them about the correct use of resources 7 , 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%